Effect of Yoga Based Lifestyle Intervention on Patients With Knee Osteoarthritis: A Randomized Controlled Trial - Deepeshwar, Singh; Tanwar, Monika; Kavuri, Vijaya; Budhi, Rana B. (Frontiers in Psychiatry, 2018)
Objective: To investigate the effect of integrated approach of yoga therapy (IAYT) intervention in individual with knee Osteoarthritis. Design: Randomised controlled clincial trail. Participants: Sixty-six individual prediagnosed with knee osteoarthritis aged between 30-75 years were randomized into two groups, i.e., Yoga (n=31) and Control (n=35). Yoga group received IAYT intervention for one week at yoga center of S-VYASA whereas Control group maintained their normal lifestyle. Outcome measures: The Falls Efficacy Scale (FES), Handgrip Strength test (left hand LHGS and right hand RHGS), Timed Up and Go Test (TUG), Sit-to-Stand (STS), and right & left extension and flexion were measured on day 1 and day 7. Results: There were a significant reduction in TUG (p<0.001), Right (p<0.001) and Left Flexion (p<0.001) whereas significant improvements in LHGS (p<0.01), and right extension (p<0.05) & left extension (p<0.001) from baseline in Yoga group. Conclusion: IAYT practice showed an improvement in TUG, STS, HGS, and Goniometer test, which suggest improved muscular strength, flexibility, and functional mobility.